Town planning and urban history in Iloilo a historiographic assessment - Madrid, Randy M. (Danyag :the UPV journal of humanities and social sciences)
"This study centered on the growing interest among historians, social scientists, local scholars, and researchers in the West Visayan region in the emerging field of urban historiography. With Iloilo City as the point of reference, a historiographic assessment and analysis of existing documents found in the universities and libraries in Iloilo has been undertaken. The development of urban historiography in Iloilo has been traced by examining the various social history works of Alfred W. McCoy, the economic and development histories of Henry F. Funtecha, studies on the development of the sugar industry by Demy Sonza, and the landscape and structural histories of this writer. Moreover, extant records, especially town planning and zoning blueprints, the City Beautiful Plans, cadastral surveys, detailed engineering studies, and city ordinance, on zoning and housing have been used as supplementary sources in data analysis and interpretation. The second part delved on a thorough discussion of colonial urbanism and the morphogenetic development of Iloilo from a weaving center to a port-of-call of inter-island and international trade and commerce in the lat 19th and early 20th centuries. Historiographic remarks from travellers' impressions and observations have been correlated with the development of microhistory focusing on Iloilo's urban development. Karl Brunner's Manual de Urbanismo has been utilized to interpret the integration of architectural and urban historiography with that of the functional planning of towns and cities as well as to single out the problems encountered by emerging urban centers. Lastly, 19th century Haussmannic urbanism has been employed by analyzing the shift of development from a microhistoric colonial city to an urban enclave fuelled by European investment and capitalist expansion. Urban reforms and renewals have been closely linked with urban modernization characterized by its sanitary reforms, residential expansion, urban design, and neighborhood revitalization. All these are collectively termed by Latin American urban historians as "Belle Epoque Reforms"."